Community-Built Databases Research and Development - Pardede, Eric (Springer eBooks., 2011)
Communities have built collections of information in collaborative ways for centuries. Most recently, Wikipedia is the most prominent example of how collaborative efforts can be powerful in building massive data storage. Other global member-built media data storage examples include Flickr and YouTube, and social networking applications such as Friendster, Facebook, and LinkedIn, which share information between members in large unstructured information pools. These platforms are obviously only small first steps, and there are many more opportunities to be unleashed using additional semantics, new interactive media, personalization, enhanced cross-references, and other approaches. There is immense potential for creating and sharing more structured data through the Web. This book, edited by Pardede, addresses the need for a comprehensive research reference on community-built databases. The contributions do not focus on only one database area or only one domain, rather they discuss various technical and social aspects of research in and development of community-built databases. In doing so they provide information on relevant research in Web science, social networks, and collaborative information systems, and they also provide pointers to further research paths. Overall, this book provides comprehensive reading material for a wide-ranging audience of researchers in database systems, Web-based collaboration tools, and Web science.